Antiviral potential of human IFN-α subtypes against influenza A H3N2 infection in human lung explants reveals subtype-specific activities. Issue 1 (1st January 2019) - Matos, Aline da Rocha; Wunderlich, Katharina; Schloer, Sebastian; Schughart, Klaus; Geffers, Robert; Seders, Martine; Witt, Marlous de; Christersson, Anmari; Wiewrodt, Rainer; Wiebe, Karsten; Barth, Peter; Hocke, Andreas; et al.
ABSTRACT: Influenza is an acute respiratory infection causing high morbidity and mortality in annual outbreaks worldwide. Antiviral drugs are limited and pose the risk of resistance development, calling for new treatment options. IFN-α subtypes are immune-stimulatory cytokines with strong antiviral activities against IAV in vitro and in vivo. However, the clinical use of IFN-α2, the only licensed subtype of this multi-gene family, could not prevent or limit IAV infections in humans. However, the other subtypes were not investigated. Therefore, this study evaluated the induction and antiviral potential of all human IFN-α subtypes during H3N2 IAV infection in human lung explants. We found that subtypes with weak antiviral activities were preferentially induced during IAV infection in human lungs. Intriguingly, non-induced subtypes α16, α5 and α4 suppressed viral replication up to 230-fold more efficiently than α2. Furthermore, our results demonstrate that subtypes with stronger antiviral activities induce higher expression of IAV-specific restriction factors and that MxA expression is a determinant of the subtype-specific antiviral activity towards H3N2 IAV. These results corroborate that IFN-α subtypes exhibit differential antiviral activities and emphasize that subtypes α16, α5 and α4 should be further investigated for the prevention and treatment of severe infections with seasonal H3N2 IAV.